Pengaruh Sosialisasi Perpajakan, Pemahaman Prosedur Perpajakan, Umur, Jenis Pekerjaan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Faris Naufal, Muhammad; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of taxation socialization, understanding of tax procedures, age, type of work to the taxpayer compliance of individuals in the Tax Office Pratama Tabanan. Population in this research is all individual taxpayer in Tax Office Primary tabanan. The number of samples used in this study as many as 100 respondents calculated based on Slovin formula with the method of determining the sample is accidental sampling method. The data were collected by using questionnaires. Data analysis technique used is multiple linier regression analysis with dummy variable. The results of this hypothesis testing indicate that the variable of taxation socialization and understanding of tax procedure have a positive effect on taxpayer compliance of individual in Pratama Tabanan Tax Office, while the variable of age and type of work have a negative effect on taxpayer compliance of individual in Tax Office Pratama Tabanan. Keywords: tax socialization, understanding tax procedure, taxpayer compliance